Letter to the editor concerning the article "Effects of acoustic feedback training in elite-standard Para-Rowing" by Schaffert and Mattes (2015) - Hill, H. (Journal of Sports Sciences, 2015)
In a case study, Schaffert and Mattes reported the application of acoustic feedback (sonification) to optimise the time course of boat acceleration. The authors attributed an increased boat speed in the feedback condition to an optimised boat acceleration (mainly during the recovery phase). However, in rowing it is biomechanically impossible to increase the boat speed significantly by reducing the fluctuations in boat acceleration during the rowing cycle. To assess such a, potentially small, optimising effect experimentally, the confounding variables must be controlled very accurately (that is especially the propulsive forces must be kept constant between experimental conditions or the differences in propulsive forces between conditions must be much smaller than the effects on boat speed resulting from an optimised movement pattern). However, this was not controlled adequately by the authors. Instead, the presented boat acceleration data show that the increased boat speed under acoustic feedback was due to increased propulsive forces.